2012
DOI: 10.4049/jimmunol.1100577
|View full text |Cite
|
Sign up to set email alerts
|

Production of Autoantibodies against Citrullinated Antigens/Peptides by Human B Cells

Abstract: Autoantibodies against citrullinated protein Ags (ACPA) are associated with the development of rheumatoid arthritis (RA). This immune response against citrullinated protein Ags, which is thought to be facilitated by certain MHC HLA-DR alleles, is highly specific for this disease and has been speculated to be involved in the pathogenesis. We have previously studied cultures of B cells for the production of Abs against HLA Ags. The aim of the current study was to examine the role of B cells in the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
(50 reference statements)
2
12
2
Order By: Relevance
“…A single study detected ACPA production in cultures of synovial fluid mononuclear cells 9. Another study identified ACPA production by peripheral blood B cells upon stimulation 10. However, it remained unclear whether ACPA detected in this latter study originated primarily from stimulated, otherwise resting memory B cells, or from circulating, differentiated plasmablasts/cells (PB/PC).…”
Section: Introductionmentioning
confidence: 81%
“…A single study detected ACPA production in cultures of synovial fluid mononuclear cells 9. Another study identified ACPA production by peripheral blood B cells upon stimulation 10. However, it remained unclear whether ACPA detected in this latter study originated primarily from stimulated, otherwise resting memory B cells, or from circulating, differentiated plasmablasts/cells (PB/PC).…”
Section: Introductionmentioning
confidence: 81%
“…Bellatin et al [31] demonstrated that B cells from RA patients produce IgG anti-CCP3 antibodies (INOVA Diagnostics, Inc.), and this production occurred in patients who had detectable anti-CCP antibodies in serum. However, normal subjects who did not have anti-CCP antibodies in serum produced anti-CCP antibodies in B-cell cultures.…”
Section: Anti-ccp Antibodies Related To Risk Factors Associated With Ramentioning
confidence: 96%
“…In addition, a DR1 allele is present in many Caucasian RA patients who are negative for DR4 alleles. All the RA-associated HLA alleles share a region of highly similar amino acid sequences (amino acids [67][68][69][70][71][72][73][74] called the shared epitope (SE), which has been postulated to control susceptibility to disease [5]. Among the important potential pathogenic peptides presented by the SE are citrullinated peptides.…”
Section: The Shared Epitope and Anti-citrullinated Protein Antibodiesmentioning
confidence: 99%
“…The changes in lymphoid architecture mediated by TNF antagonists may contribute to the reductions in memory B cells noted in RA patients treated with these therapies [62,65,66], which may be important, as memory B cells in RA patients express anti-CCP autoantibodies [67]. In addition, TNF antagonists decrease the proportion of memory B cells expressing CD86 after 6 months of therapy [68].…”
Section: Tnf-a Blockadementioning
confidence: 99%